Halqa Arbab e Zoq, Meera Ji and the modern concept of Urdu Nazm - Dr. Shabbir Hussain; Dr. Muhammad Kamran (Zaban-o-Adab, 2023)
This article reads the relationship between Halq e Arbab e Zoq and Modern Poet, Meera Ji. This aims at reviewing the paradigm shift that happened in the genre of Urdu Nazm and how the brilliant creative mind of Meera Ji Contributed in it regarding Subject matter, Symbolism, Structure and development of other aspects of Urdu Nazm. Halq e Arbab e Zoq was oriented towards innovation from the beginning and all the topics which were merely related to external factors, their justification for the circle also existed somewhere in internal experiences. But Miraji’s involvement in the circle of Halq e Arbab e Zoq, where the circle became a movement, it kept the concept of modern poetry, independent poetry and poetry fresh and wide and new to an extent that was not possible in Urdu poetry before. In this sense, Miraji’s joining the Halq e Arbab e Zoq was not an unusual event. What was most prominent and unique among the writers of Halq e Arbab e Zoq circle was freshness and innovation. The addition of this freshness and innovation was found in the form of Miraji. That’s why Miraji and Halq e Arbab e Zoq became references to each other.